Unique Highly Nonlinear Photonic Crystal Fibers with Ultra-flattened Chromatic Dispersion and Low Confinement Loss - Begum, Feroza; Abas, Pg Emeroylariffion; Kabir, Izaddeen (International Journal of Advanced Science and Technology, 2019)
This paper proposes and investigates a unique highly nonlinear dispersion flattened photonic crystal fibre (HNDF-PCF) via numerical simulation using full vector finite difference method (FDM). Simulation results have shown that it is possible to obtain high nonlinear coefficient of higher than 51 W-1km-1 at 1.55 μm wavelength, near-zero ultra-flattened chromatic dispersion of 0 ± 0.4 ps/(nm.km) covering the E+S+C+L telecommunication bands, low chromatic dispersion slope of -0.003 ps/(nm2.km) and very low confinement loss of less than 10-7 dB/km between 1.4 μm and 1.65 μm wavelength. These results point to suitability of the proposed HNDF-PCF to be used in data communication system.